2020
DOI: 10.2147/ijn.s230879
|View full text |Cite
|
Sign up to set email alerts
|

<p>G250 Antigen-Targeting Drug-Loaded Nanobubbles Combined with Ultrasound Targeted Nanobubble Destruction: A Potential Novel Treatment for Renal Cell Carcinoma</p>

Abstract: Purpose: We intended to design G250 antigen-targeting temsirolimus-loaded nanobubbles (G250-TNBs) based on the targeted drug delivery system and to combine G250-TNBs with ultrasound targeted nanobubble destruction (UTND) to achieve a synergistic treatment for renal cell carcinoma (RCC). Methods: The filming-rehydration method was combined with mechanical shock and electrostatic interactions to prepare temsirolimus-loaded nanobubbles (TNBs). G250-TNBs were prepared by attaching anti-G250 nanobodies to the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…While destructive probes do not provide spatial information on detected cavitation, aside from that inferred from behavior and time delays, it is possible that active delivery enhances intact NB penetration into tumors under the tested conditions: Indeed it has recently been shown that targeted NBs under ultrasound exposure are able to achieve deep penetration into rabbit clots, and with greater efficacy than stimulated MBs 67 . Ultrasound stimulation of NBs has also been shown to enhance delivery and penetration of co-injected or loaded drugs in various preclinical tumor models 10 , 11 , 48 , 49 and for blood-brain-barrier disruption 7 , 8 , though intact NB extravasation was not validated and microscale events were not visualized. A plethora of ultrasound parameters have been used, typically with frequencies between 1-10 MHz, durations on the order of a few minutes, but greatly varying acoustic pressures from 100 kPa to several MPa.…”
Section: Resultsmentioning
confidence: 99%
“…While destructive probes do not provide spatial information on detected cavitation, aside from that inferred from behavior and time delays, it is possible that active delivery enhances intact NB penetration into tumors under the tested conditions: Indeed it has recently been shown that targeted NBs under ultrasound exposure are able to achieve deep penetration into rabbit clots, and with greater efficacy than stimulated MBs 67 . Ultrasound stimulation of NBs has also been shown to enhance delivery and penetration of co-injected or loaded drugs in various preclinical tumor models 10 , 11 , 48 , 49 and for blood-brain-barrier disruption 7 , 8 , though intact NB extravasation was not validated and microscale events were not visualized. A plethora of ultrasound parameters have been used, typically with frequencies between 1-10 MHz, durations on the order of a few minutes, but greatly varying acoustic pressures from 100 kPa to several MPa.…”
Section: Resultsmentioning
confidence: 99%
“…Nanobubbles coupled with nanobodies targeting the prostate-specific membrane antigen (PSMA) facilitated prostate cancer imaging by ultrasonography [148]. Anti-G250 nanobody-bearing targeted nanobubbles improved ultrasound imaging of renal cell carcinomas in mouse models [149,150]. Anti-eGFP (cAbGFP4) and the clinically translatable anti-VCAM-1 (cAbVCAM1-5) nanobodies have been employed for tailoring microbubbles to improve their targeting and imaging potential both in vitro and in vivo [151,152].…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…18 Despite this prior work showing poor NB echogenicity, recent in vivo tumor CEUS imaging studies using NBs have concluded that NBs are echogenic. [19][20][21][22][23] We hypothesize that this discrepancy can be explained by MB contamination in the NB suspensions. Prior CEUS studies have demonstrated that total bubble volume fraction is a more accurate prediction of in vitro and in vivo echogenicity than number concentration.…”
Section: Introductionmentioning
confidence: 93%